MEASURING THE EFFECTIVENESS OF SECTOR ROTATION INVESTMENT STRATEGY IN SELECTED LISTED COMPANIES IN INDONESIA USING SHARPE RATIO, TREYNOR RATIO AND JENSENÃâÃâS ALPHA - PARULIAN AMBARITA (NIM 29112056) Pembimbing : Ir. Subiakto Soekarno, MBA, ALBERT
This study examines the application of sector rotation investment strategy in Indonesia Stock Exchange. In certain economic condition, one sector can perform better than the other sector. Principle of this investment strategy is investing in sectors that perform better than the other. Performance of one sector has strong correlation with economic condition and business cycle used to describe the economic condition. There are two methods that used to identify business cycle, conventional and proposed method. Both methods will be compared to find what is the best methods to identify business cycle. Indicator that used to compare the methods is risk adjusted return. Method with higher risk adjusted method is the best method to identify business cycle. Indicators that used to compare risk adjusted return are Sharpe Ratio, Treynor Ratio, and JensenÃ‚Â’s Alpha. This investment strategy also compared with passive strategy by investing in Jakarta Composite Index. Performance of every sector over business cycle examined from 2000-2012. Phase of business cycle divided to three periods: Early Expansion, Late Expansion, and Recession. The phases identified from historical data of macroeconomic. Macroeconomic indicator that used to to identify the business cycle are global GDP, Indonesia GDP, and inflation rate in Indonesia. Interestingly, global GDP has larger impact to Indonesia capital market than Indonesia GDP itself, so global GDP used as main source to identify business cycle in Indonesia. Every business cycle phase has different duration, depend on the change on economic condition. Portfolio simulation that implement the sector rotation investment strategy is built after choose the best sector in every business cycle phase. The most liquid and largest capitalization stock is selected from LQ 45 Index. Proposed method generate higher ending investment value than proposed method and proposed method also generate better risk adjusted return. From the result can be conclude that proposed method is better than conventional method in identify business cycle. Risk adjusted return generated from applicating the strategy regardless the method that used is higher than return of Jakarta Composite Index. That means that sector rotation investment strategy appication in Indonesia Stock Exchange is effective.